0092 Necessity of Sleep for Motor Gist Learning in Mice. (27th April 2018) - Pettibone, W D; Kam, K; Varga, A W
Abstract: Introduction: The benefits of sleep toward cognition are not limited to memory consolidation; human studies have shown that sleep also augments extraction of the general idea of a task, or its "gist." Gist learning has never been studied in animals, however. The goals of the current study are to test whether gist extraction is possible in a mouse model and to understand the role of sleep in gist extraction of a motor task. Methods: Mice completed 10 consecutive rotarod trials per session with a 3-minute inter-trial interval, running exclusively forward or exclusively backward by narrowing dividers over the rod. Rod acceleration was 4–40 RPM over 5 minutes, and latency to fall was measured. Performance running backward for the first time (naïve) was compared to 3 alternative conditions: 1) backward performance following 2 days running forward at ZT 0 followed by ad libitum sleep, 2) backward performance following 2 days running forward at ZT 0 followed by 10 hours of sleep disruption (SD), and 3) backward performance following 2 sessions running forward on 1 day, where only 20 minutes of natural wake existed between sessions. During acute SD experiments, SD was achieved using an automated sensory stimulus every 10 seconds for 10 hours between ZT 2 and 12. Results: Running exclusively forward followed by ad libitum sleep for two days (20 trials total) imparts significant gains in backward running performance compared to naïve mice, and gains did not occur if exclusive forward running was followed by SD. Natural wake after acquisition of forward running template behavior is insufficient to impart the benefit of gist extraction toward exclusive backward running, even when total number of trials is the same. Conclusion: Motor gist learning is possible in a mouse after two days of exposure to template behavior. The extraction of gist appears to depend on sleep. Acute SD impairs gains in backward running ability seen in mice allowed to sleep, and these gains do not occur during natural wake. This represents the first demonstration of gist learning in an animal model. Support (If Any):